Characteristics of Thymine Molecule System Behave as Molecular Electronic Device - Shakir A. A. AL-Saidi, Alaa Ayad K. Al-mebir, Mohammed Hallool ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2019)
The I-V characteristics of thymine are presented by using tightbinding model with steady state. The current as function of gate voltage which is varying between -4 to 4 eV is plotted. Also, the tunneling phenomena is appeared into the features of molecules. The appliance of gate voltage shows good ON/OFF keying of the two applied voltages- bias voltage and gate voltage. In our work the thymine molecule is proposed as a turn on and turn off key, MOSFET properties can be used in thymine molecular electronic devices. Further, the magnetic flux has been studied for transmission, current and conductance.